Peran Empowerment dalam Meningkatkan Komitmen Organisasional dan Kinerja Karyawan - Aldisa Arifudin (Musamus University, Merauke Papua Indonesia., 2019)
Organization as a logical arrangement of the activities of a number of people in order to achieve targets through the division of tasks and functions of levels and responsibilities. HR issues are still a concern for companies to continue to survive in the era of globalization. To be able to carry out tupoksi, it requires empowerment in order to achieve organizational commitment to be achieved so that the desired performance of PT Wedu Merauke can proceed and arouse passion and work spirit for its members. To find out the triggers for the decline in employee performance levels, the authors are encouraged to carry out research with the title the role of empowerment in increasing organizational commitment and employee performance. With a population and a sample of 70 people. The method used is primary data that focuses information related to variables. Such as observation, interviews and questionnaires. And secondary data focus on explanations compiled from existing sources. like through other people or documentation. Data analysis was performed using partial tests, determination tests, and path analysis. The results obtained are that as the increase in empowerment increases organizational commitment because of the tcount > ttable (3.073 > 1.99547) and the significance level of empowerment for organizational commitment is smaller than the significance level (0.003 < 0.05). The more effective empowerment will create performance employees increased because of tcount > ttable (3.127 > 1.99547) and the significance level of empowerment on employee performance was smaller than the significance level (0.003 < 0.05), if organizational commitment was embedded in each employee to have a positive impact on employee performance due to tcount > ttable (4,345 > 1,99547) and the significance level of empowerment on organizational commitment is smaller than the significance level (0,000 < 0,05), if there is a change in empowerment through organizational commitment it will result in a change in performance due to an indirect value of 0,157